Innovation, competition and productivity: Firm‐level evidence for Eastern Europe and Central Asia1. Issue 3 (28th May 2016) - Friesenbichler, Klaus; Peneder, Michael
Abstract: We investigate the drivers of firm‐level productivity in catching‐up economies by jointly estimating its relationship to innovation and competition using data from the EBRD‐WB Business Environment and Enterprise Performance Survey (BEEPS) in Eastern Europe and Central Asia. The findings confirm an inverted‐U shaped impact of competition on R&D. Both competition and innovation have a simultaneous positive effect on labour productivity in terms of either sales or value added per employee, as does a high share of university graduates and foreign ownership. Further positive impacts come from firm size, exports or population density. Innovation and foreign ownership appear to be the strongest drivers of multifactor productivity.